DIGITAL TRANSFORMATION OF KOREAN LANGUAGE TEACHING: INSIGHTS FROM KF E-SCHOOL PROGRAMS (SCIENCE TIME JOURNAL, 2026)
This study investigates the digital transformation of Korean language teaching through the implementation of KF e-School programs within a hybrid learning environment in Uzbekistan. The research is based on a four-month instructional period involving 14 undergraduate students enrolled in academic writing and speaking courses. A mixed-methods approach was employed to evaluate student performance, engagement, and perceptions of digital learning. The findings demonstrate that the integration of video-on-demand (VOD) lectures with face-to-face instruction significantly enhances language acquisition, particularly in writing structure, speaking fluency, and learner motivation. However, several challenges were identified, including technical limitations and the need for localized pedagogical support. Overall, the KF e-School model shows strong potential for expanding Korean language education through digital innovation and hybrid methodologies